Combined inhibition of morphogen pathways demonstrates additive antifibrotic effects and improved tolerability - Distler, Alfiya; Lang, Veronika; Del Vecchio, Tina; Huang, Jingang; Zhang, Yun; Beyer, Christian; Lin, Neng-Yu; Palumbo-Zerr, Katrin; Distler, Oliver; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2014)
The morphogen pathways Hedgehog, Wnt and Notch are attractive targets for antifibrotic therapies in systemic sclerosis. Interference with stem cell regeneration, however, may complicate the use of morphogen pathway inhibitors. We therefore tested the hypothesis that combination therapies with low doses of Hedgehog, Wnt and Notch inhibitors maybe safe and effective for the treatment of fibrosis.Skin fibrosis was induced by bleomycin and by overexpression of a constitutively active TGF-? receptor type I. Adverse events were assessed by clinical monitoring, pathological evaluation and quantification of Lgr5-positive intestinal stem cells.Inhibition of Hedgehog, Wnt and Notch signalling dose-dependently ameliorated bleomycin-induced and active TGF-? receptor type I-induced fibrosis. Combination therapies with low doses of Hedgehog/Wnt inhibitors or Hedgehog/Notch inhibitors demonstrated additive antifibrotic effects in preventive as well as in therapeutic regimes. Combination therapies were well tolerated. In contrast with high dose monotherapies, combination therapies did not reduce the number of Lgr5 positive intestinal stem cells.Combined inhibition of morphogen pathways exerts additive antifibrotic effects. Combination therapies are well tolerated and, in contrast to high dose monotherapies, may not impair stem cell renewal. Combined targeting of morphogen pathways may thus help to overcome dose-limiting toxicity of Hedgehog, Wnt and Notch signalling.
EVALuna2:12898